ChemInform Abstract: A Polystyrene‐Supported, Highly Recyclable Squaramide Organocatalyst for the Enantioselective Michael Addition of 1, 3‐Dicarbonyl Compounds to β‐Nitrostyrenes. Issue 15 (25th March 2013) - Kasaplar, Pinar; Riente, Paola; Hartmann, Caroline; Pericas, Miquel A.
Abstract A chiral squaramide supported onto a polystyrene resin is used as a very active, easily recoverable and highly reusable organocatalyst for the asymmetric Michael addition of 1, 3‐dicarbonyl compounds to β‐nitrostyrenes.